Pengaruh Kurs Dollar Amerika, Jumlah Produksi Dan Luas Lahan Pada Volume Ekspor Lada Indonesia - Fitri, Ida Ayu Diah; Purbadharmaja, Ida Bagus Pt (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
The international trade it’s one of the efforts to overcome the problems of a country in meeting community needs. One of them is the pepper that has great potential in the international market. This study examines the influence of the USA dollar exchange rate, the amount of land area in the production and export volume of Indonesian pepper. The this ressearch used a secondary data from the years 1993 to 2012 times series. Based on the data analysis technique multiple linear regression known US dollar exchange rate, the amount of production and land simultaneously influence on Indonesian pepper export volume in 1993-2012. While partially , only the variable number of production and positive influence land area , while US dollar exchange rate has no effect on the export of pepper Indonesia in 1993-2012
Keywords: kurs dollar USA; produksi; ekspor